Role of PGC-1α mediated synaptic plasticity, mitochondrial function, and neuroinflammation in the antidepressant effect of Zi-Shui-Qing-Gan-Yin - Zhu, Wen; Zhang, Wen; Yang, Feng; Cai, Min; Li, Xiangting; Xiang, Yijin; Xiang, Jun; Yang, Yunke; Cai, Dingfang (Frontiers in Neurology, 2023)
Depression is the most prevalent psychiatric disorder, which needs deeper mechanism research studies and effective therapy. Zi-Shui-Qing-Gan-Yin (ZSQGY) is a traditional Chinese medicine decoction that has been widely used in China in the treatment of depressive symptoms. The aim of the study was to examine the anti-depressive effects of ZSQGY and the possible mechanism of action in the monosodium glutamate (MSG)-induced depressive model and the corticosterone (CORT)-induced PC12 cell model. Liquid chromatography-mass spectrometry (LC–MS) was performed to determine the major compounds in the water extract of ZSQGY. The depressive behaviors were evaluated by the field swimming test (FST), the sucrose preference test (SPT), and the open field test (OFT). Golgi staining and transmission electron microscopy (TEM) were performed to display the alterations of synaptic ultrastructure. The mitochondrion function and inflammatory factors were also quantified. The changes in peroxisome proliferator-activated receptor-γ co-activator 1α (PGC-1α) expression were evaluated. The results of this study demonstrated that ZSQGY significantly improved depressive behaviors. ZSQGY also reversed the changes in synaptic plasticity, improved mitochondrion function, and reduced the levels of inflammatory factors. The neuroprotective effects were accompanied by the increased expression of PGC-1α. However, the beneficial changes were reversed after the inhibition of PGC-1α. These results indicated that ZSQGY effectively could improve depressive behaviors via the mechanisms that regulate synaptic structural plasticity, improve mitochondrion function, and alleviate neuroinflammation, which could, or partly, attribute to the regulation of PGC-1α.